E-ACTIVE AGING study protocol: Evaluating an exergame-based and multicomponent exercise program for community-dwelling older adults at risk of falling - Lillo-Urzúa, Paloma; Ugarte-Llanten, Jorge; Carreño-Zilmann, Gabriel; Vidal-Seguel, Nicolás; Guede-Rojas, Francisco; Cuenca-García, Magdalena; Cigarroa, Igor (Frontiers in Physiology, 2025)
BackgroundFalls among older adults represent a major cause of morbidity and mortality, leading to decreased physical activity, loss of independence, and increased dependency. Individuals aged 60 years and older, particularly those with sensory deficits, are at greater risk. While conventional fall-prevention programs are widely implemented, innovative strategies such as active exergames have emerged as promising approaches to enhance balance and reduce fall risk.ObjectiveThis study aims to evaluate the effectiveness of a supervised exergame-based multicomponent intervention compared to a traditional multicomponent training program in community-dwelling older adults at risk of falling.MethodsA randomized controlled trial with parallel groups and blinded assessment will be conducted among older adults (≥60 years) recruited from senior centers (SENAMA, Chile). Fifty-two participants will be randomly allocated to either an exergame group (n = 26), performing interactive full-body movements using the Nintendo Switch®, or a traditional multicomponent training group (n = 26). Both groups will receive 1-h supervised sessions twice weekly for 12 weeks. The primary outcomes will include fall risk, balance performance, functional independence and cardiorespiratory fitness. Secondary outcomes will assess body composition, muscular strength and quality, physical activity level, quality of life, and pain intensity and interference.Expected ResultsIt is hypothesized that both interventions will improve functional and balance outcomes, with the exergame-based program potentially promoting greater adherence and superior overall effects.Clinical Trial RegistrationClinicalTrials.gov. Identifier: NCT07024004.